PENGARUH ORIENTASI PERUSAHAAN DAN SOCIAL MISSION ERA GLOBALISASI DALAM KONTEKS KEBERLANGSUNGAN USAHA TERHADAP GREEN EKONOMI - I Made Tawan; I Dewa Nyoman Usadha; I Kadek Dony Wishanesta (Nusantara Hasana Journal, 2024)
This research aims to determine the influence of company orientation on the Social mission of the era of globalization, determine the influence of company orientation on the green economy and determine the influence of company orientation on the Social mission of the era of globalization and the green economy. This research uses mixed research methods, specifically an explanatory sequential design. Creswell (2022:1088) defines mixed methods research design as a method for collecting, analyzing, and combining qualitative and quantitative research methodologies in one study. The results of this research are that first, company orientation (X1) has a positive and significant effect on the Social mission of MSMEs (Y) at Pia Kukus Made Bali with a calculated t value of 5,876 > t table 1,983 and a significance probability value of 0.000 < 0.05, with a Beta coefficient has a positive result of 0.301. This illustrates that the influence of company orientation (X1) can improve the Social mission of MSMEs (Y). Secondly, Green economy (X2) has a positive and significant effect on the Social mission of MSMEs (Y) at Pia Kukus Made Bali with a calculated t value of 8.555 > t table 1.983 and a significance probability value of 0.000 < 0.05, with the Beta coefficient having a positive result of 0.521. This illustrates that the influence of the green economy (X2) can improve the Social mission of MSMEs (Y). The third is company orientation (X1) and green economy (X2) together (simultaneously) have a positive and significant effect on the Social mission of MSMEs (Y) at Pia Kukus Made Bali with a calculated F value of 62,243 > 3,090 F table and a significance probability value as much as 0.000 < 0.05. This illustrates that the influence of company orientation (X1) and green economy (X2) together can improve the Social mission of MSMEs (Y).